Analysis of Phonetic Language Disorder in Patients with Aphasia - Inggrit Meili; Arlisma Faida Niarti; Lusiana Suciati Dewi (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Communication is the main medium for conveying information or a message. Communication does not work well when an individual experiences communication disorders, for example, language disorders. Language disorders are disorders or damage that attack the brain in the Broca and Wernicke areas so that the language acquisition process is not optimal. One of these language disorders is called aphasia. This research aims to find out how people with aphasia communicate, especially when they have difficulty pronouncing certain words or letters. This research uses descriptive qualitative methods using interviews and observations as research instruments. The individual who was resource person in this research was a woman who was diagnosed with aphasia as a result of an accident so she had to experience difficulties in communicating.